Sanksi Administratif sebagai Primum Remidium Pelanggaran Pemanfaatan Ruang Laut: Efek Jera atau Negosiasi: Administrative Sanctions as a Primary Remedy for Violations in Marine Space Utilization: A Deterrent Effect or Negotiation - Anam, Saiful; Priyo Amboro, Yudhi; Shahriyani Shahrullah, Rina (Faculty of Law Hang Tuah University, 2025)
One form of control over the utilisation of marine space is the imposition of administrative sanctions. However, the number of violations in the past four years (2021–2024) has shown a continuous increase each year, with a significant rise in 2024. The aim of this study is to evaluate the administrative sanctions on violations of marine spatial utilisation as a form of Primum Remedium. This research employs an empirical legal research method using the analytical tools of the Theory of Legal Effectiveness and the Integrative Law Theory. Data were collected through interviews and secondary data gathering, then analysed using qualitative juridical techniques. The findings indicate that only the legal factor can be considered effective, whereas law enforcement, infrastructure, society, and cultural factors still face obstacles that hinder the successful implementation of administrative sanctions. Therefore, regulatory simplification and an increase in the number of law enforcement officers are needed, as well as enhanced public education.